Model‐Informed Pediatric Dose Selection for Dapagliflozin by Incorporating Developmental Changes - Jo, Heeseung; Pilla Reddy, Venkatesh; Parkinson, Joanna; Boulton, David W.; Tang, Weifeng (CPT: pharmacometrics and systems pharmacology, 2021)
This analysis reports a quantitative modeling and simulation approach for oral dapagliflozin, a primarily uridine diphosphate‐glucuronosyltransferase (UGT)–metabolized human sodium‐glucose cotransporter 2 selective inhibitor. A mechanistic dapagliflozin physiologically based pharmacokinetic (PBPK) model was developed using in vitro metabolism and clinical pharmacokinetic (PK) data and verified for context of use (e.g., exposure predictions in pediatric subjects aged 1 month to 18 years). Dapagliflozin exposure is challenging to predict in pediatric populations owing to differences in UGT1A9 ontogeny maturation and paucity of clinical PK data in younger age groups. Based on the exposure–response relationship of dapagliflozin, twofold acceptance criteria were applied between model‐predicted and observed drug exposures and PK parameters (area under the curve and maximum drug concentration) in various scenarios, including monotherapy in healthy adults (single/multiple dose), monotherapy in hepatically or renally impaired patients, and drug–drug interactions with UGT1A9 modulators, such as mefenamic acid and rifampin. The PBPK model captured the observed exposure within twofold of the observed monotherapy data in adults and adolescents and in special population. As a guide to determining dosing regimens in pediatric studies, the verified PBPK model, along with UGT enzyme ontogeny maturation understanding, was used for predictions of dapagliflozin monotherapy exposures in pediatric subjects aged 1 month to 18 years that best matched exposure in adult patients with a 10‐mg single dose of dapagliflozin.